Intratechal Chemotherapy Treatment Through an Ommaya Reservoir Catheter for Meningeal Carcinomatosis: A Single-Centre Experience - Lavrador, José Pedro; Simas, Nuno; Oliveira, Edson; Carvalho, Manuel Herculano (Acta Médica Portuguesa, 2016)
Introduction: Meningeal carcinomatosis is defined as tumour cells infiltration of leptomeninges and subarachnoid space. It is normally related with poor survival (2 - 5 months). The best multidisciplinary treatment for this condition is a matter of discussion. Patient’s condition and the natural history of the disease should be considered in the decision making process. Material and Methods: Retrospective cohort analysis of patients submitted to Ommaya Reservoir placement due to systemic solid tumour meningeal carcinomatosis between 2006 and 2014. Results: Twenty three patients were included (19 females, four males) with median age of 56.1 ± 2.2 years. The primary tumour was: breast – 16 patients, lung – four patients, stomach, bladder and cervix – one patient each. No complications were seen (infection, intracranial haematoma or CSF fistula). The median survival was 26.4 ± 7.7 weeks, range between nine days and 118 weeks (21/23 patients). Male gender was related to poor prognosis in crude analysis (p value = 0.0032). Breast adenocarcinoma was related with better prognosis in adjust analysis (p value = 0.036, HR: 4.36 ± 3.06; 95% IC: 1.10 - 17.25). Longer time between initial tumour and meningeal carcinomatosis diagnosis was related to a better outcome but without statistical significance. Discussion: Despite the low complication rate of Ommaya reservoir placement, the poor response to chemotherapy and the disease prognosis should be considered in patients with poor functional status. The relationship observed between the primary tumour and the overall survival supports that meningeal carcinomatosis should not be considered a disease by itself but always in the context of a systemic disease. The low incidence of breast cancer in male population might be related with it poorer prognosis. Conclusion: Meningeal carcinomatosis has a poor prognosis. Breast adenocarcinoma, longer time between initial tumour and meningeal carcinomatosis diagnosis, and age < 60 years were related with longer survival.